Alternative Approaches to IEP Conflict: A Review of the Literature - Sinkonis, Laura (Journal of the American Academy of Special Education Professionals, 2017)
The originators of special education law anticipated disputes and provided due process hearings as a means to settle the disputes. However, due process proved to be unfair, costly (financially and emotionally), and destructive to school-family relationships. Years later, lawmakers offered mandated mediation along with resolution meetings in attempts to lessen the usage of due process. While the number of due process hearings has decreased, mediation and resolution meetings may occur too late in the resolution process to repair broken trust and communication in relationships between families and school districts. Alternative dispute resolution strategies offer means to end conflicts sooner, less expensively, and with fewer damaged relationships.